Pulsed laser diode based optoacoustic imaging of biological tissues - Upputuri, Paul Kumar (2015)
Optoacoustic tomography (OAT) is a promising hybrid imaging modality for many biomedical applications. However, the use of Nd:YAG laser as excitation source makes the OAT system expensive, and non-portable. Miniaturization of OAT system is an immediate task to make it a potential tool for both preclinical and clinical studies. In this work, we present an OA system that uses a miniaturized pulsed laser diode which can provide near infrared pulses at ~803 nm. With laser fluence ~0.3 mJ cm−2 on the tissue surface, we achieved 3 cm deep imaging in chicken tissue. The high pulse repetition rate of the diode laser allowed rapid acquisition of OA cross-sectional images with good image quality. The results promise that the proposed system has potential to be used as an alternative to Nd:YAG based OAT systems for biological imaging applications.